Gastrointestinal regulation of food intake - David E. Cummings; Joost Overduin (The Journal of Clinical Investigation, 2007)
Despite substantial fluctuations in daily food intake, animals maintain a remarkably stable body weight, because overall caloric ingestion and expenditure are exquisitely matched over long periods of time, through the process of energy homeostasis. The brain receives hormonal, neural, and metabolic signals pertaining to body-energy status and, in response to these inputs, coordinates adaptive alterations of energy intake and expenditure. To regulate food consumption, the brain must modulate appetite, and the core of appetite regulation lies in the gut-brain axis. This Review summarizes current knowledge regarding the neuroendocrine regulation of food intake by the gastrointestinal system, focusing on gastric distention, intestinal and pancreatic satiation peptides, and the orexigenic gastric hormone ghrelin. We highlight mechanisms governing nutrient sensing and peptide secretion by enteroendocrine cells, including novel taste-like pathways. The increasingly nuanced understanding of the mechanisms mediating gut-peptide regulation and action provides promising targets for new strategies to combat obesity and diabetes.